Enhanced corticomuscular coherence by external stochastic noise - Trenado, Carlos; Mendez-Balbuena, Ignacio; Manjarrez, Elias; Huethe, Frank; Schulte-Mönting, Jürgen; Feige, Bernd; Hepp-Reymond, Marie-Claude; Kristeva, Rumyana (Frontiers in Human Neuroscience, 2014)
Noise can have beneficial effects as shown by the stochastic resonance phenomenon which is characterized by performance improvement when an optimal noise is added. Modern attempts to improve human performance utilize this phenomenon. The purpose of the present study was to investigate whether performance improvement by addition of optimum noise is related to increased cortical motor spectral power and increased corticomuscular coherence. Eight subjects performed a visuomotor task requiring to compensate with the right index finger a static force generated by a manipulandum on which Gaussian noise was applied. The finger position was displayed on-line on a monitor as a small white dot which the subjects had to maintain in the center of a green bigger circle. Electroencephalogram from the contralateral motor area, electromyogram from active muscles and finger position were recorded. The performance was measured by the mean absolute deviation of the white dot from the zero position. Optimum noise compared to the zero noise condition induced an improvement in motor accuracy together with an enhancement of cortical motor spectral power and corticomuscular coherence in beta-range. These data suggest that the improved sensorimotor performance via stochastic resonance is consistent with an increase in the cortical motor spectral power and in the corticomuscular coherence.